Repressing Egypt's civil society: State violence, restriction of the public sphere, and extrajudicial persecution - Jannis Grimm (Stiftung Wissenschaft und Politik (SWP), 2015)
Since the military coup of July 2013, one of the characteristics of the Egyptian regime has been the lack of clarity on the boundaries of political activism and on what activities it would, or would not, tolerate. Red lines have been shifting frequently, as a plethora of presidential decrees has restricted the public sphere ever more. Furthermore, state institutions and investigating bodies have increasingly abused their powers against civil society representatives. Torture, arbitrary detention and enforced disappearances have become recurrent phenomena. Embattled by State Security, a politicized judiciary and competing ministries, human rights activists are less and less able to fulfil their role as watchdogs. From being merely the witnesses of assaults and human rights violations by the security forces, they have moved on to being their primary targets. Against this backdrop, Germany and its European partners should pressure the Egyptian authorities for compliance with basic civil rights and the rule of law, while aligning their support more closely with the needs of Egyptian NGOs. (SWP Comments)
Keywords: 320